2009
DOI: 10.1139/h08-147
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the brain of nicotine-induced toxicity: protective role ofAndrographis paniculataNees and vitamin E

Abstract: Mitochondria are the crossroads of several crucial cellular activities; they produce considerable quantities of superoxide radical and hydrogen peroxide, which can damage important macromolecules. Nicotine affects a variety of cellular processes, from induction of gene expression to modulation of enzymatic activities. The aim of this study was to elucidate the protective effects of andrographolide (ANDRO) aqueous extract (AE-Ap) of Andrographis paniculata, and vitamin E on nicotine-induced brain mitochondria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 70 publications
4
67
0
Order By: Relevance
“…This result was consistent with previous studies depicting that protein oxidation was elevated in cigarette smoke exposure Das et al 2009;Fraga et al 2011;Ozkol et al 2012). It was already showed that cigarette smoke causes increased generation of free radicals, mainly ROS, through the induction of various ROSproducing endogenous enzymes (Deliconstantinos and Villiotou 2000;Czekaj et al 2005;Das et al 2009;Khanna et al 2013;Jaques et al 2013). In agreement with their reports, the present results illustrated that Cyt P450, NADPH oxidase, and XO activities were increased in the brain of rats exposed to cigarette smoke.…”
Section: Discussionsupporting
confidence: 94%
“…This result was consistent with previous studies depicting that protein oxidation was elevated in cigarette smoke exposure Das et al 2009;Fraga et al 2011;Ozkol et al 2012). It was already showed that cigarette smoke causes increased generation of free radicals, mainly ROS, through the induction of various ROSproducing endogenous enzymes (Deliconstantinos and Villiotou 2000;Czekaj et al 2005;Das et al 2009;Khanna et al 2013;Jaques et al 2013). In agreement with their reports, the present results illustrated that Cyt P450, NADPH oxidase, and XO activities were increased in the brain of rats exposed to cigarette smoke.…”
Section: Discussionsupporting
confidence: 94%
“…It is well known that nicotine contributes a major proportion of the net oxidative stress imposed by tobacco use. Nicotine induced oxidative stress in rat brain tissue has also been reported (18). Additionally, nicotine exposure significantly increased lipid peroxidation in various tissues of rats (19).…”
Section: Introductionmentioning
confidence: 75%
“…Nicotine has been shown to produce nitric oxide, which suppresses the mitochondrial oxidative stress scavenger system in different brain regions (18). Antioxidant effects of vitamin E and C have been reported against prenatal nicotine induced oxidative stress effects in rats and in monkeys (18,22).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that alloxan is selectively toxic to pancreatic beta cells, leading to the induction of cell necrosis (6) . The cytotoxic action of alloxan is mediated by reactive oxygen species, with a simultaneous massive increase in cytosolic calcium concentration, leading to rapid destruction of beta cells (12) .…”
Section: Discussionmentioning
confidence: 99%